The study of hearing threshold of workers in an industrial company: A comparison of those who wear earplugs correctly and those who do not - Marwa Faisal Alalawi, Salman Mohamed Alsendi, Abdulla Abdulrazaq Almahmood, Salim Isa Alothman, Saleh Ismaeel Alrowaili, Saad Mohammed Saad, Noof Sami Aljirdabi, Aldana Mohd Zayed, Faisal Abdulaziz Almannaie, Abdulla Ali Khaled, Atheer Shams-aldin Othman; Ahmed Abdelkarim Jaradat (Journal of Medical Care Research and Review, 2021)
The aim of this study was to compare the outcome between workers who wore earplugs correctly compared to those who do not. Our objective was to observe whether the company’s worker is wearing earplugs correctly or not, and to obtain the audiometrical data concerning those who wore an earplug correctly compared to those who do not. The study was conducted in a company held in Bahrain at summer 2016. The type of study which was conducted was cross-sectional study which is a type of observational study that involves the analysis of data collected from the company workers who wear earplugs correctly and the experimental group who wear them incorrectly. The method which was used was an assessment sheet and an audiometrical device which is a machine that evaluates hearing acuity and determines the degree and type of hearing activity. The assessment sheet included the worker’s personal data (name, badge number and department), information regarding the use of earplugs correctly or not, and the audiometrical results. The major findings that we found from our results is that there’s a signification association between wearing earplugs and department only. However, there is no correlation between wearing ear plugs correctly and age, position and occupation. In conclusion, the workers that wore the ear plugs correctly had a better hearing threshold then those who did not. With the majority of worker who had hearing loss were from the oil and processing department, which is known to be the noisiest department. Keywords: Hearing, earplug, hearing loss.